ANALISIS IMPLEMENTASI TANGGAP DARURAT BENCANA UNTUK MENUNJANG BUSINESS CONTINUITY PERUSAHAAN MANUFAKTUR - Sufa, Kathya Irsmi; Lestantyo, Daru; Kurniawan, Bina (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
The development of the industry at this time entered the industrial revolution 4.0 which is supported by all forms of information technology. Emergency response is a form of management effort in protecting production activities in the company and avoiding the risk of accidents, it has in common with the principle of business continuity. The purpose of this study is to analyze disaster emergency response to support the business continuity of manufacturing companies. This research is qualitative, data collection techniques using in-depth interviews with three main informants and two triangulation informants. The results of this study include training, implementation and policy, communication, life-saving facilities, organization and business continuity, and finding conditions that still need attention from forms of training, communication, and organization regarding occupational safety and health in the disaster emergency response process to support the application of business continuity planning. The training provided by the company is under the standards, but there are still shortcomings from the involvement of management. The communication provided by the company is not active, communication is conveyed when there is something that needs to be conveyed. The organization has P2K3 and emergency response, but there is still no equal distribution of emergency response structures in each unit of the manufacturing company.